Survey for Serum Neuraminidase, Free and Erythrocyte Surface Sialic Acid from Chickens Vaccinated Against Newcastle Disease and the Unvaccinated Chickens Reared under Semi-Intensive Management System - Oladele, Sunday Blessing; Abdu, Paul; Nok, Andrew Jonathan; Esievo, King Akpofure Nelson (International Journal of Poultry Science, 2007)
The study was carried out to determine the levels of neuraminidase, erythrocyte surface and free serum sialic acid concentrations of chickens that were vaccinated against Newcastle Disease (ND) and unvaccinated chickens reared under semi-intensive management system in Zaria metropolis. A total of one hundred chickens, fifty each from vaccinated and unvaccinated flocks, randomly selected from ten backyard poultry farms were used for the study. Neuraminidase activity and concentrations of erythrocyte surface and free serum sialic acids were determined for each chicken, using thiobarbituric acid assay method. The values of Packed Cell Volume (PCV) and antibody titres to Newcastle Disease Virus (NDV) were also determined for each chicken by microhaematocrit and Haemagglutination Inhibition (HI) methods, respectively. The mean neuraminidase activity (4.514±1.70 μmol/min) and free serum sialic acid concentration (0.075±0.03 mg/ml) obtained from the vaccinated chickens were significantly higher (p